EXPERIMENTAL STUDY IN PRIMARY WOOD CUTTING WITH CIRCULAR SAW AND BAND SAW MACHINE - Atanasov, Valentin (Innovation in Woodworking Industry and Engineering design, 2021)
Experimental research on some performance indicators of a circular saw machine (Kallion Konepaja Oy – Finland) for longitudinal cutting of logs were performed. The accuracy of the machine operation and the roughness of the boards were measured successively. For this purpose, the feed speed vf was varied widely, from 4 to 100 m.min-1 . The test specimens are of beech wood (Fagus silvatica L.). The research place was the manufacturing facility of Pentop Ltd. – Varshets. The results were analyzed and compared with those obtained previously with а band saw machine.